2017
DOI: 10.1101/143750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction (or not) during language processing. A commentary on Nieuwland et al. (2017) and DeLong et al. (2005)

Abstract: We would like to thank both DeLong and colleagues and Nieuwland and colleagues for sharing additional information about their studies with us, and for answering our many questions. We would also like to express that the points we raise in this manuscripts have not undergone peer review and should thus not be used to interfere with the publication of Nieuwland et al. (2017), which is still under review.. CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 77 publications
6
42
0
Order By: Relevance
“…Ito, Martin, and Nieuwland likewise obtained a marginally significant ( p = 0.06) prediction N400 effect at a/an articles for native English‐speaking participants (see discussion in DeLong, Urbach, & Kutas, ). An exception to these findings is a controversial multilab experiment by Nieuwland et al (), which reported a failed replication of the DeLong et al study (see Yan, Kuperberg, & Jaeger, , and a blog post by Shravan Vasishth, : https://vasishth-statistics.blogspot.com/2017/04/a-comment-on-delong-et-al-2005-nine.html for elaboration).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ito, Martin, and Nieuwland likewise obtained a marginally significant ( p = 0.06) prediction N400 effect at a/an articles for native English‐speaking participants (see discussion in DeLong, Urbach, & Kutas, ). An exception to these findings is a controversial multilab experiment by Nieuwland et al (), which reported a failed replication of the DeLong et al study (see Yan, Kuperberg, & Jaeger, , and a blog post by Shravan Vasishth, : https://vasishth-statistics.blogspot.com/2017/04/a-comment-on-delong-et-al-2005-nine.html for elaboration).…”
Section: Introductionmentioning
confidence: 95%
“…Ito, Martin, and Nieuwland likewise obtained a marginally significant (p = 0.06) prediction N400 effect at a/an articles for native English-speaking participants (see discussion in DeLong, Urbach, & Kutas, 2017). An exception to these findings is a controversial multilab experiment by Nieuwland et al (2018), which reported a failed replication of the DeLong et al study (see Yan, Kuperberg, & Jaeger, 2017, Critically, others, using the same basic experimental paradigm as DeLong et al (2005), have taken their data as support for morphosyntactic prediction during sentence comprehension. These studies relied on gender-marked languages such as Spanish (Foucart, Martin, Moreno, & Costa, 2014;Wicha, Bates, et al, 2003;Wicha, Moreno, & Kutas, 2004) and Dutch (Van Berkum et al, 2005;Otten & Van Berkum, 2008) to show that readers and listeners preactivate specific upcoming nouns, as evidenced by amplitude modulations of ERPs to prenominal grammatical-gender-marked articles or adjectives.…”
mentioning
confidence: 95%
“…Despite its explanatory success, the idea that predictive expectations explain online processing is not uncontroversial, and many crucial details remain unsettled. For instance, there is currently some vivid debate concerning the specific contextual cues that may trigger predictions, and about how specific and generalizable such predictions are (DeLong, Urbach, & Kutas, ; Ito, Martin, & Nieuwland, ; Yan, Kuperberg, & Jaeger, ). Moreover, it is astonishing that the vast majority of studies to date focuses on syntactic or lexical–semantic processing with much less emphasis on genuine pragmatic aspects (but see Werning & Cosentino, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because, while the N400 resulting from semantic incongruities is typically maximal in the centro-parietal region of the brain (Brown & Hagoort, 1993; Kutas & Federmeier, 2011), violations in metrical/phonological expectancies more commonly result in a N400 that is more frontally located (e.g. Böcker et al, 1999; DeLong et al, 2005; Lau et al, 2008; Steinhauer & Connolly, 2008; Rothermich et al, 2010, 2012; Yan et al, 2017), we selected fronto-central and centro-parietal electrodes (Fpz, FCz, Fz, AFz, Fp1, Fp2, FC1, FC2, F1, F2, AF3, AF4, Cz, P1, P2, C3, C4, Pz, P3, P4, CP1, CP2). Furthermore, because the phonological/metrical N400 has been reported to precede the semantic N400 temporally (e.g.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Note that while the post-lexical integration theory may reject anticipatory processes and consider the N400 to index exclusively post-lexical processes initiated upon perceiving the target word, it not necessarily needs to; one can easily imagine integration processes to also benefit from successful (semantic) anticipation based on prior contextual information (as is pointed out by Yan et al 2017, see also Kuperberg & Jaeger 2016 and Nieuwland et al 2018). …”
mentioning
confidence: 99%